2009
DOI: 10.1017/s1041610208008211
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver factors contributing to psychological elder abuse behavior in long-term care facilities: a structural equation model approach

Abstract: These findings should be incorporated into practice by intervening to reduce caregiver stress and reduce elder abuse behaviors. To help reduce elder psychological abuse, caregivers would benefit from stress management and social resource interventions provided by employers or government programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 20 publications
3
27
0
2
Order By: Relevance
“…In contrast, higher risk of being “neglected, abused and mistreated” was observed among older adults with their primary caregiver experienced a lower level of informal support. A previous study in Taiwan has also found a positive association in this sense . Among the three relationship factors, only one significant relationship between conflicting relationship and “fearful of a family member or caregivers” was found in the current study, which was in line with the conclusion by the systematic review and extended to a Chinese context, as few studies in the Asian region had examined the association between conflicting relationship and different forms of potential abuse .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, higher risk of being “neglected, abused and mistreated” was observed among older adults with their primary caregiver experienced a lower level of informal support. A previous study in Taiwan has also found a positive association in this sense . Among the three relationship factors, only one significant relationship between conflicting relationship and “fearful of a family member or caregivers” was found in the current study, which was in line with the conclusion by the systematic review and extended to a Chinese context, as few studies in the Asian region had examined the association between conflicting relationship and different forms of potential abuse .…”
Section: Discussionsupporting
confidence: 91%
“…Limpawattana et al reported that older caregivers with poorer self-reported health status, a longer of duration of care, and a lower self-reported income had higher caregiver burdens, such as stress and depression [8]. Studies have also shown that negative care reactions by caregivers lead to negative impacts, such as caregiver depression, poor quality of care, potentially harmful behavior, and elder abuse [6], [14], [35]. Burdened caregivers have reported less social support, poorer quality of life, and problems with social integration [36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, knowledge may maximize the quality of caring behavior and decrease the potential negative effects on caregivers. Caregivers with negative caring behavior, overloaded caregiver burdens, and a lack of caring knowledge lead to negative patient health and health promotion behavior outcomes [6], [12][14]. Therefore, the caregivers' caring behavior, caregiver burden, and caring knowledge may inevitably affect the patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, large number of co-residing days with older adults (Yan, 2014a;Yan & Kwok, 2011), a lack of assistance from a domestic helper (Yan & Kwok, 2011), a high level of caregiver burden (Yan, 2014a;Yan & Kwok, 2011) childhood experience of abuse, negative attitudes toward older adults, and modernity (Yan & Tang, 2003) were significantly linked to elder abuse. In Taiwan, fewer working hours of caregivers, lower education level, lack of social resources, higher working stress (Wang, Lin, Tseng, & Chang, 2009), caregiver burden, and younger age (Wang, 2005;Wang, Lin, & Lee, 2006) were identified as key factors associated with psychological elder abuse behavior.…”
Section: Potential Perpetrator Characteristicsmentioning
confidence: 99%